Outcomes of Early Development of Hyponatremia in Acute ST-Elevated Myocardial Infarction Patients: A Study in a Tertiary Hospital (University Heart Journal, 2020)
Background: Coronary heart disease is a global health problem and a major cause of death in both developed and developing countries. Clinical importance of hyponatremia in ST-elevated acute myocardial infarction (STEMI) is an important topic of study among present researchers.Objective: To assess the outcomes and prognostic implications of early development of hyponatremia inhospitalized acute ST-elevated myocardial infarction patients.Methods: This is a prospective observational study performed in the department of Cardiology, Combined Military Hospital (CMH), Dhaka from July 2018 to June 2019. A purposive sampling technique was used on 82 patients with ST-elevated acute myocardial infarction admitted in CCU and treated with thrombolysis. They were evaluated for serum sodium level at admission and at 48 hours after admission. Here sodium concentration